Quantity and Physicochemical Analysis of Biodiesel from CPO Processed by Electrolysis Method - Muhammad Dhafir; Darwin Darwin; Muhammad Alwi Al Fayed; Siti Suharyatun (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Biodiesel is produced by esterification-transesterification, using alcohol as a reactant and acid and base catalysts. Electrocatalyst is a method to increase production yield by utilizing H+ and OH– ions as a catalyst. This study aims to investigate the biodiesel production process through the esterification-transesterification reaction and analyze the physicochemistry of biodiesel produced from CPO by electrolysis using platinum electrodes. CPO was esterified-transesterified and then analyzed the production yield and physicochemistry of biodiesel. Rsults showed that the highest biodiesel yield was produced at a voltage of 6 V, which is 88.67%, the lowest acid value and moisture content of biodiesel was produced from a voltage of 12 V are 0.99 mgKOH/g and 0.75%, the kinematic viscosity that met the SNI biodiesel standards resulted in a voltage of 6 V and without the use of electrolysis, namely 3.53 cSt and 3.63 cSt, and the highest flash point value for biodiesel is produced from a voltage of 12 V, which is 109 ° C.   Keywords:  Biodiesel, Crude palm oil (CPO), Electrolysis, Physicochemical, Platinum.